Kyai Haji Abbas Abdul Jamil’s Da’wa Model: The Combination Between Tradition Aspects with Psychosufism - Amirudin; Jajat Darojat; Wajd, Farid; Karim, Abdul; Hidayat, Amin; Royyani, Mohammad Fathi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2023)
This article discusses the religious thoughts of K.H. Abbas Abdul Jamil regarding manhaj in carrying out preaching and social approaches and solutions to problems in society. Since the literature discussing the figure of K.H. Abbas Abdul Jamil Buntet mostly talks about his struggle and heroism, this research aims to explain the other side of K.H. Abbas Abdul Jamil regarding religious thought and his approach to society. The researchers used a qualitative approach to discuss K.H. Abbas Abdul Jamil's thoughts. Data were obtained through interviews with families and santri (students)/alums regarding daily life and how to educate santri. The data were then analyzed with related literature. The results of this study revealed that, among others, the approach to society taken by K.H. Abbas Abdul Jamil in carrying out his preaching mission was through a shar’i approach by applying qawā'id fiqhiyyah and an approach to the culture and habits of the community. In conclusion, societal problems need to be solved using the right approach. K.H. Abdul Jamil intelligently used his qawā'id fiqhiyyah analysis skills and socio-cultural approaches as his manhaj preaching.